Molecular pathology of cutaneous melanoma. (November 2014) - van Kempen, Léon C; Redpath, Margaret; Robert, Caroline; Spatz, Alan
SUMMARY : Cutaneous melanoma is associated with strong prognostic phenotypic features, such as gender, Breslow's thickness and ulceration, although the biological significance of these variables is largely unknown. It is likely that these features are surrogates of important biological events rather than directly promoting cutaneous melanoma progression. In this article, we address the molecular mechanisms that drive these phenotypic changes. Furthermore, we present a comprehensive overview of recurrent genetic abnormalities, both germline and somatic, in relation to cutaneous melanoma subtypes, ultraviolet exposure and anatomical localization, as well as pre-existing and targeted therapy-induced mutations that may contribute to resistance. The increasing knowledge of critically important oncogenes and tumor-suppressor genes is promoting a transition in melanoma diagnosis, in which single-gene testing will be replaced by multiplex and multidimensional analyses that combine classical histopathological characteristics with the molecular profile for the prognostication and selection of melanoma therapy.